2021
DOI: 10.3233/wor-203411
|View full text |Cite
|
Sign up to set email alerts
|

Work addiction as a predictor of anxiety and depression

Abstract: Background: A worker’s work habits can affect their health, both physically and psychologically. Negative results have been associated with work demands (stress, anxiety and depression). Objective: In the present research we carried out a predictive Study of Work Addiction by applying three questionnaires on depression and anxiety. Methods: In this study, the participants were 332 workers, obtained through non-probabilistic sampling. The FACTOR (version 7.2) and SPSS 23.0 programs were used. Results: The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In addition, a recent study cast light on the role of job control as defined by decision-making autonomy in modulating workaholism and emotional exhaustion ( Spagnoli and Molinaro, 2020 ). Far from being a trivial issue, workaholism deserves attention as it is considered a predictor of anxiety and depression ( Serrano-Fernández et al, 2021 ), physical health problems and strained social relationships, and poor job performance in the long run ( Ng et al, 2007 ; Clark et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a recent study cast light on the role of job control as defined by decision-making autonomy in modulating workaholism and emotional exhaustion ( Spagnoli and Molinaro, 2020 ). Far from being a trivial issue, workaholism deserves attention as it is considered a predictor of anxiety and depression ( Serrano-Fernández et al, 2021 ), physical health problems and strained social relationships, and poor job performance in the long run ( Ng et al, 2007 ; Clark et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with the available literature data, we found that WA was significantly and positively associated with psychological distress, in terms of depression (Bartczak & Ogińska-Bulik, 2012 ; Quinones & Griffiths, 2015 ), anxiety (Bartczak & Ogińska-Bulik, 2012 ; Robinson, 1999 ), and stress (Bartczak & Ogińska-Bulik, 2012 ; Quinones & Griffiths, 2015 ; Schaufeli et al, 2009b ). Serrano-Fernández et al (Serrano-Fernández et al, 2021 ) have recently showed that WA variables (i.e., excessive work and feelings generated by work) helped to predict 18.3% of depression and 20.3% of anxiety in Spanish workers. However, we emphasize that, due to the cross-sectional nature of the analysis, we are unable to suggest causality.…”
Section: Discussionmentioning
confidence: 99%
“…There is enough empirical data to support the relationships between FA, WA, and psychological distress of clinical relevance in young adults (Piccinni et al, 2021 ; Serrano-Fernández et al, 2021 ). On the other hand, it has been suggested that the interrelationship of work, food patterns, and disease is subject to cultural and social shaping (Schulte et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Workaholism is related to personality traits such as perfectionism and Type A personality [4] as well as low self-esteem [13]. Workaholics, especially females, are more likely to experience negative affect [18,19] and anxiety [19,20]. Workaholism is also positively associated with job demands, role conflict, and job control, and negatively related to role clarity [21].…”
Section: Workaholism Overviewmentioning
confidence: 99%